Simulação dinâmica da produção de biossurfactantes pelas bactérias Pseudomonas aeruginosa e Pseudomonas fluorescens utilizando modelo cinético de Monod - Silva, Mariana Julia Gomes da (Universidade Federal de São Carlos, 2022)
Surfactants are tensoative compounds with amphipathic characteristics, due to the presence of hydrophilic and hydrophobic structures in the same molecule, which gives them the property of distributing themselves between two immiscible phases from the reduction of interfacial and surface tension. The production of these molecules can come from synthetic or biological routes, with the synthetic route using petroleum derivatives and the biological route using cellular metabolites or enzymes. The exploration of the microbiological route comes from the growing environmental concern for the substitution of petroleum-based products by less polluting ones, because the surfactants produced by the chemical route have greater toxicity to living beings and its application may result in environmental contamination of soils and aquatic environments. In comparison, biosurfactants have biodegradable and non-toxic characteristics, may have higher surfactant power than those from the synthetic route, and are stable over a wide range of temperature, pH, and ionic strength. This work is a literature review on surfactants, biosurfactants and their main uses in the industry, especially in the petrochemical industry. In addition, the objective was to model and simulate the production of biosurfactant by respiration, using the free software Scilab 6.1.1. By defining a kinetics for consumption of the two substrates (heavy petroleum fractions, n-Hexadecane and n-Eicosane), for cell growth of two biosurfactant-producing bacteria (Pseudomonas aeruginosa and Pseudomonas fluorescens bacteria) and accumulation of bioproduct (Ramnolipid biosurfactant), a system of ordinary differential equations was organized, based on Monod's kinetic model proposed by Sakthpriya et al. (2016). The results obtained reinforce the possibility of using the two bacteria for the degradation of these heavy hydrocarbon fractions, evidenced by the consumption of substrate mass as a function of the formation of new biosurfactants. Even with a low productivity for industrial application, the analysis from the low yield data, which was calculated from the average biomass produced per unit of substrate mass consumed (g.g-1), had the highest quantitative production with n-Eicosane as substrate and P. aeruginosa as bacterial cell, reaching the concentration of 0.12 g.L-1. For the model developed with the High Yield values, the highest concentration of biosurfactant used n-hexadecane as substrate and P. aeruginosa as bacteria, reaching a maximum concentration of 5.45 g.L-1.
Dynamic simulation of biosurfactant production by Pseudomonas aeruginosa and Pseudomonas fluorescens bacteria using Monod's kinetic model
Keywords: Biossurfactantes; Pseudomonas aeruginosa; Pseudomonas fluorescens; n-Hexadecano; n-Eicosano; Biosurfactants; n-Hexadecane; n-Eicosane; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA